Contemporary information social risks in the post-modern era - L. V. Tcerkasevich; E. A. Makarenko (Управление)
The article analyses the global social risks related to the expansion of information technologies, mass digitalisation, and the accessibility of sources of all information. The possibility of risky situations arising in different areas of society under postmodern conditions has been demonstrated. This is due to the massive spread of information and Internet technology, global changes in the structure of values of modern society, and the reassessment of a number of historical events and characters by some social groups. The focus is on the destruction of traditional mechanisms for transmitting social experience and memory and the transformation of perceptions of history through the use of virtual forms of communication. A different, own interpretation of historical events, the liberation of historical knowledge from politicisation and mythologisation can lead to risks of distortion of historical memory and even to conflicting situations of interpretation of the past. Case studies show that this, in turn, can lead to a set of risks in the economic sphere, for example: the risk of a situation of global redistribution of economic resources, the risk of losing the source of legitimacy of an economic resource, the risk of loss the reputation of a memory entity. These processes negatively affect social stability in society and distort the integrity of historical memory.Particular attention is paid to the topic of cognitive transformation risk related to the mass use of virtual media in the educational process. On the one hand, they are an effective teaching tool based on rapid search, transformation and storage of learning information. But, on the other hand, practice shows that knowledge loses its consistency and becomes “mosaic”, “clichéd”. The consequences of these processes are of a lasting nature and require further in-depth study by the scientific community, including psychologists, educators, and sociologists.